Synthesis of dibenzo[a, j]phenazine compounds using hemicucurbit[6]uril‐catalyzed oxidative dimerization of 2‐arylamines. Issue 22 (17th September 2020) - Li, Heng; Yu, Juan; Ge, Qingmei; Liu, Mao; Tao, Zhu; Cong, Hang
Abstract: A supramolecular catalytic strategy for the synthesis of dibenzo[ a, j ]phenazine compounds from 2‐arylamines is demonstrated. The dimerization is achieved through the catalytic action of HemiQ[6] in an acidic environment. Kinetic constants and activation energies have been calculated through UV/Vis spectrophotometric investigations using different amounts of HemiQ[6], whereby the reactivity was found to be related to the electron densities of the substrates. A possible mechanism involving host‐guest interaction between a 2‐arylaminium salt and HemiQ[6] through hydrogen‐bonding is proposed. The transformation of 2‐arylamines to dibenzo[ a, j ]phenazines in the presence of HemiQ[6] suggests that such supramolecular catalysis is effective for such constructions. Abstract : A supramolecular strategy for the facile synthesis of dibenzo[ a, j ]phenazine compounds from 2‐arylamines was achieved in the presence of hemicucurbit[6]uril with assistance of acid in high yield and selectivity, and the kinetic analysis was performed. A possible mechanism was proposed based on the analysis of control experimental results. The dimerization products exhibited very strong fluorescence, which could be applied for potential emission materials.